A composite welding method for resisting electrochemical corrosion of a rare earth pipeline steel

CN122913627APending Publication Date: 2026-10-16SHANDONG IRON & STEEL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611341605.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-01
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0004]目前,现有管线焊接防腐工艺存在一系列难以克服的缺陷

Benefits of technology

(1)构建了“电化学匹配稀土焊丝+分段动态脉冲焊接+超声冲击-电化学原位钝化”三重耦合复合焊接体系,解决了稀土管线钢焊接接头电位不均、易发生电偶腐蚀、焊缝耐蚀性差的技术问题。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application discloses a rare earth pipeline steel anti-electrochemical corrosion composite welding method, and relates to the technical field of pipeline welding. The rare earth pipeline steel anti-electrochemical corrosion composite welding method adopts an electrochemical matching Ce-La mixed rare earth modified welding wire, cooperates with a gradient heat input welding process of pulse MIG backing, double-pulse TIG layered filling and surface covering, combines with ultrasonic impact nanocrystallization and rare earth electrochemical in-situ passivation composite post-processing, and constructs a multi-process coupling strengthening system. The welding seam and the base material can be precisely matched in electrochemical potential, the galvanic corrosion of the welded joint can be eliminated, the welding seam microstructure can be refined, and the Fe-Ce composite passivation film with self-repairing characteristics can be formed on the welding seam surface, so that the corrosion resistance and the overall mechanical stability of the welded joint are significantly improved. The process is simple and controllable, and has good on-site adaptability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of pipeline welding technology, and in particular relates to a composite welding method for rare earth pipeline steel to resist electrochemical corrosion. Background Technology

[0002] Rare earth pipeline steel, due to its excellent strength, toughness, weldability, and corrosion resistance, has been widely used in long-distance oil and gas pipelines, chemical pipelines, and marine engineering. Rare earth elements (REs) in steel can significantly improve its corrosion resistance by purifying grain boundaries, modifying inclusions, and microalloying. However, welding, as the primary connection method in pipeline steel field construction, creates uneven microstructures in the weld joint area due to intense thermal cycling. These areas include the weld metal (WM), fusion zone (FZ), coarse-grained heat-affected zone (CGHAZ), fine-grained heat-affected zone (FGHAZ), and partial phase transformation heat-affected zone (ICHAZ), making them sensitive areas for electrochemical corrosion.

[0003] Existing research indicates that significant galvanic corrosion effects occur in different regions of pipeline steel welded joints due to differences in microstructure: the weld metal is typically cast with coarse grains and severe compositional segregation, exhibiting a negative corrosion potential and thus easily acting as an anode for accelerated corrosion; while the heat-affected zone, due to the presence of coarse bainite / martensite-austenite (MA) components, exhibits high localized corrosion susceptibility. This is particularly true in Cl-containing areas. - In corrosive media environments such as CO2 and H2S, the electrochemical inhomogeneity of welded joints leads to local corrosion rates that are much higher than those of the base material, becoming a major cause of pipeline failure.

[0004] Currently, existing pipeline welding corrosion protection processes suffer from a series of insurmountable defects. First, conventional welding wire designs mostly focus on matching mechanical properties, neglecting the corrosion potential matching between the weld and the base metal, as well as the heat-affected zone. This leads to the natural formation of macroscopic electrocouples at the joint, exacerbating weld corrosion. Second, the methods for controlling welding heat input are relatively limited. Simply increasing heat input to improve corrosion resistance often results in coarse grains and deteriorated joint toughness, making it difficult to simultaneously achieve both mechanical properties and corrosion resistance. Furthermore, existing technologies lack post-weld in-situ electrochemical control processes suitable for field operations. Conventional post-weld heat treatment or external protective coatings have high construction thresholds and cannot fundamentally eliminate the inherent electrochemical inhomogeneities at the joint. Finally, rare earth elements in the base metal are easily burned off at the high welding temperatures and are unevenly distributed within the weld, making it difficult to fully utilize their role in refining the microstructure and improving corrosion resistance.

[0005] In summary, existing single welding or single protection methods cannot simultaneously solve multiple problems such as potential mismatch between weld and base material, difficulty in balancing strength and corrosion resistance in welding heat input, segregation of rare earth element welding burn-off, and lack of on-site adaptable in-situ electrochemical homogenization treatment. As a result, the problem of joint galvanic corrosion failure cannot be effectively suppressed from the root cause. Summary of the Invention

[0006] To address some or all of the technical problems existing in the prior art, this application provides a composite welding method for rare earth pipeline steel to resist electrochemical corrosion, using rare earth pipeline steel as the base material and employing a special welding wire, comprising the following steps: Step S1, Pre-welding treatment: Grind and clean the steel bevel and both sides of the rare earth pipeline to remove oxide scale, oil and impurities, and expose the metal luster. Step S2, Pulsed MIG root pass welding: Pulsed gas inert metal arc welding is used for root pass welding. The heat input is controlled at 0.8~1.2kJ / mm to obtain a uniform and fine composite structure of acicular ferrite and granular bainite in the root pass weld. Step S3, Double-pulse TIG filler and capping weld: Using AC double-pulse tungsten inert gas (TIG) shielded welding, intermediate filler weld and surface capping weld are sequentially performed on the root weld. The heat input of the intermediate filler weld is controlled at 1.0~1.3 kJ / mm, so that the filler weld forms a microstructure mainly composed of acicular ferrite. The heat input of the surface capping weld is controlled at 1.2~1.5 kJ / mm, so that the capping weld forms a microstructure mainly composed of equiaxed ferrite with dispersed carbonitride precipitates. Step S4, Ultrasonic Impact Nanoscale Treatment: After welding, use an ultrasonic impact gun to impact the weld surface and the heat-affected zone within 15-25mm on both sides. The impact frequency is 20-28kHz, the impact amplitude is 30-50μm, and the impact is repeated 2-4 times at a speed of 150-300mm / min to make the surface coverage of the treated area ≥95%, thereby forming a nanocrystalline layer with a grain size of 10-100nm and a thickness of 50-200μm on the weld surface. Step S5, Electrochemical In-situ Passivation Treatment: Utilizing the high-density grain boundaries in the nanocrystalline layer formed in Step S4 as nucleation sites for the passivation film, constant potential electrochemical passivation treatment is performed on the weld surface. The treatment solution is a mixed solution of 0.5~2.0 mol / L NaNO3 and 0.1~0.5 mol / L Ce(NO3)3, with a solution temperature of 40~60℃, a constant potential of +0.2~+0.6V (vs. SCE), and a treatment time of 10~30 min. A composite passivation film containing CeO2 and Ce2O3 is formed on the weld surface, resulting in a rare earth pipeline steel welded joint.

[0007] Preferably, the welding wire is a Ce-La mixed rare earth modified low alloy high-strength steel welding wire, with the following chemical composition by mass percentage: C 0.03~0.06%, Si 0.20~0.40%, Mn 1.10~1.50%, Cr 0.50~0.55%, Ni 1.10~1.25%, Mo 0.35~0.40%, Cu 0.25~0.30%, Nb 0.035~0.040%, Ti 0.012~0.015%, S≤0.004%, P≤0.010%, with the balance being Fe and unavoidable impurities; Ce and La in the welding wire constitute mixed rare earth RE, the total mass fraction of Ce and La is 0.015%~0.030%, and the mass ratio of Ce to La is (60~70):(30~40).

[0008] Preferably, the rare earth pipeline steel base material has the following chemical composition by mass percentage: C 0.04~0.07%, Si 0.20~0.35%, Mn 1.40~1.65%, Cr 0.35~0.40%, Ni 0.25~0.30%, Mo 0.15~0.18%, Cu 0.20~0.22%, Ce and La total rare earth RE mass fraction of 0.010%~0.015%, Nb 0.040~0.045%, Ti 0.015~0.018%, S≤0.005%, P≤0.015%, with the balance being Fe and unavoidable impurities.

[0009] Preferably, in step S2, the process parameters for pulsed MIG root pass welding are: wire diameter φ1.0~1.2mm, peak current 280~350A, base current 80~120A, pulse frequency 80~150Hz, pulse duty cycle 35%~50%, welding speed 25~40cm / min, and shielding gas is a ternary mixture of Ar + 2%~5%CO2 + 0.5%~1.5%O2.

[0010] Preferably, in step S3, the process parameters for the dual-pulse TIG filler and capping welding are: tungsten electrode diameter φ2.4~3.2mm; main pulse peak current 180~240A, main pulse base current 60~90A, main pulse frequency 50~80Hz; secondary pulse peak current 220~280A, secondary pulse base current 40~60A, secondary pulse frequency 2~5Hz; welding speed 15~25cm / min; shielding gas is a nitrogen-rich mixture of Ar + 3%~8% N2.

[0011] Preferably, the ultrasonic impact treatment in step S4 introduces a residual compressive stress layer with a depth of 400~600μm on the surface of the weld, and the maximum residual compressive stress is -300~-500MPa.

[0012] Preferably, the ultrasonic impact treatment in step S4 reduces the surface roughness Ra of the weld from 12~20μm in the welded state to 2~4μm.

[0013] Preferably, in step S4, the ultrasonic impact treatment uses an impact needle with a diameter of φ2 to 4 mm to perform reciprocating impact.

[0014] Preferably, in step S5, the constant potential electrochemical passivation treatment adopts a three-electrode system, with the working electrode being the weld itself, the auxiliary electrode being a Pt sheet, and the reference electrode being a saturated calomel electrode.

[0015] Preferably, the welded joint is placed in a 3.5wt% NaCl corrosion solution, and the self-corrosion potential difference between the weld area and the base material is ≤30mV.

[0016] The composite welding method for resisting electrochemical corrosion of rare earth pipeline steel proposed in this application has the following advantages and positive effects: (1) A triple-coupled composite welding system of “electrochemical matching rare earth welding wire + segmented dynamic pulse welding + ultrasonic impact-electrochemical in-situ passivation” was constructed, which solved the technical problems of uneven potential, easy galvanic corrosion and poor corrosion resistance of rare earth pipeline steel welded joints.

[0017] (2) By precisely controlling the electrochemical properties of the weld seam using Ce-La mixed rare earth modified welding wire, the self-corrosion potential difference between the weld seam and the base material is stably controlled within 30mV, eliminating macroscopic galvanic corrosion. Relying on the oxygen sulfides and nitrides generated by rare earths, the weld seam grains are refined and grain boundary defects are purified, reducing microscopic corrosion galvanic cells and achieving uniform electrochemical performance across the entire joint, breaking the drawback of "preferential corrosion of the weld seam" in traditional welding. At the same time, ultrasonic nano-sizing and rare earth electrochemical passivation form a significant synergistic effect, constructing a dense, self-healing Fe-Ce composite gradient passivation film on the weld seam surface, effectively resisting chloride ion erosion, significantly reducing the corrosion rate of the welded joint, and greatly improving the corrosion resistance of the joint.

[0018] (3) A gradient heat input process of "low heat input for the base layer - medium heat input for the filling layer - medium-high heat input for the top layer" is adopted, combined with dual-pulse electromagnetic stirring, nitrogen solid solution strengthening and AC cathodic cleaning technology, which effectively suppresses grain coarsening, eliminates welding inclusion defects, and obtains a uniform and fine gradient fine grain structure, ensuring that the joint has excellent strength and toughness. Ultrasonic impact treatment can effectively offset the residual tensile stress of welding, optimize the surface roughness, introduce stable residual compressive stress, and significantly reduce the risk of stress corrosion and localized corrosion. The whole process is simple, does not require post-weld heat treatment and additional protective coating, and can be adapted to the on-site construction of various rare earth pipeline steels, ensuring that the joint has both excellent corrosion resistance and mechanical properties while reducing construction costs. Detailed Implementation

[0019] To make the objectives, technical solutions, and advantages of this application clearer, the technical solutions of this application will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only a part of the embodiments of this application, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of this application without creative effort are within the scope of protection of this application.

[0020] The composite welding method for resisting electrochemical corrosion of rare earth pipeline steel in this application uses rare earth pipeline steel as the base material and special welding wire for welding. The welding wire is a Ce-La mixed rare earth modified low alloy high-strength steel welding wire, with the following chemical composition by mass percentage: C 0.03~0.06%, Si 0.20~0.40%, Mn 1.10~1.50%, Cr 0.50~0.55%, Ni 1.10~1.25%, Mo 0.35~0.40%, Cu 0.25~0.30%, Nb 0.035~0.040%, Ti 0.012~0.015%, S≤0.004%, P≤0.010%, with the balance being Fe and unavoidable impurities; Ce and La in the welding wire constitute mixed rare earth RE, with a total mass fraction of Ce and La of 0.015%~0.030%, and a Ce to La mass ratio of (60~70):(30~40). This welding wire achieves potential matching control through the synergistic compounding of four corrosion-resistant alloying elements: Cr, Ni, Mo, and Cu. Cr enhances the density of the passivation film, Ni stabilizes the matrix structure, Mo strengthens resistance to pitting corrosion, and Cu promotes the formation of a dense corrosion product film. This combination controls the self-corrosion potential difference between the weld and the base metal to within 30mV, eliminating the macroscopic galvanic effect between them. The 0.015%–0.030% Ce-La mixed rare earth element in the welding wire provides microalloying strengthening. After entering the weld pool, the rare earth elements combine with oxygen and sulfur to generate dispersed rare earth oxysulfides (RE2O2S). These sulfides purify grain boundaries, reduce pitting corrosion sources induced by sulfide inclusions, and act as nucleation sites to promote the nucleation of acicular ferrite, refining the weld microstructure and improving its uniformity. Meanwhile, the welding wire adopts a low carbon design of 0.03~0.06%, which can suppress the formation of coarse proeutectoid ferrite and MA corrosion-sensitive phases; S≤0.004% can fundamentally reduce MnS inclusions and reduce pitting corrosion sensitivity; combined with the nano-scale carbonitrides pinning grain boundaries precipitated by Nb and Ti elements, it can suppress the coarsening of weld metal grains, promote the nucleation of intragranular acicular ferrite, and improve the strength, toughness and corrosion resistance of weld metal.

[0021] The chemical composition of the rare earth pipeline steel base material, by mass percentage, is as follows: C 0.04~0.07%, Si 0.20~0.35%, Mn 1.40~1.65%, Cr 0.35~0.40%, Ni 0.25~0.30%, Mo 0.15~0.18%, Cu 0.20~0.22%, Ce and La total rare earth (RE) mass fraction 0.010%~0.015%, Nb 0.040~0.045%, Ti 0.015~0.018%, S≤0.005%, P≤0.015%, with the balance being Fe and unavoidable impurities. An appropriate amount of Ce-La mixed rare earth is pre-added to the base material, giving it basic corrosion resistance. This allows it to form an electrochemically matched combination with the aforementioned welding wire alloy system. Combined with the gradient welding process proposed in this application, the uniformity of the electrochemical performance across the entire weld joint can be achieved.

[0022] Specifically, the steps include the following: Step S1, Pre-welding treatment: Grind and clean the bevel and both sides of the rare earth pipeline steel to remove oxide scale, oil and impurities, and expose the metallic luster.

[0023] The purpose of the pretreatment process is to remove foreign contaminants such as oxide layer, oil, and rust from the bevel surface, avoid porosity and slag inclusion defects during welding, prevent local component segregation at the fusion interface from forming micro-corrosion cells, and ensure a clean and continuous fusion interface between the weld and the base material.

[0024] Step S2, Pulsed MIG root pass welding: Pulsed gas metal arc welding is used for root pass welding. The heat input is controlled at 0.8~1.2kJ / mm to obtain a uniform and fine composite structure of acicular ferrite and granular bainite in the root pass weld. The process parameters for pulsed MIG root pass welding are: wire diameter φ1.0~1.2mm, peak current 280~350A, base current 80~120A, pulse frequency 80~150Hz, pulse duty cycle 35%~50%, welding speed 25~40cm / min, and shielding gas is a ternary mixture of Ar + 2%~5%CO2 + 0.5%~1.5%O2.

[0025] The system employs alternating high and low pulsed currents. During the peak phase, it achieves stable droplet transfer and ensures complete penetration at the pipe root. During the base phase, it extends the cooling time of the weld pool. The overall heat input is 0.8~1.2 kJ / mm, significantly lower than the conventional MIG welding range of 1.5~2.5 kJ / mm. This effectively suppresses overheating and coarsening of the weld root grains, resulting in a uniform and fine composite structure of acicular ferrite and granular bainite in the root pass. The addition of trace amounts of O2 to the shielding gas improves the fluidity of the weld pool, promotes the full fusion reaction of rare earth elements in the welding wire, reduces high-temperature burn-off of rare earth elements, and increases rare earth yield. Simultaneously, it forms a thin, dense oxide film on the weld root surface, reducing the susceptibility to localized corrosion at the root.

[0026] Step S3, Double-Pulse TIG Filler and Cover Welding: Using AC double-pulse tungsten inert gas (TIG) welding, intermediate filler welding and surface cover welding are performed sequentially on the root weld. The heat input for the intermediate filler welding is controlled at 1.0~1.3 kJ / mm to form a microstructure dominated by acicular ferrite in the filler weld. The heat input for the surface cover welding is controlled at 1.2~1.5 kJ / mm to form a capping weld dominated by equiaxed ferrite with dispersed carbonitride precipitates. The microstructure of the phase; the process parameters for double-pulse TIG filler and capping welding are: tungsten electrode diameter φ2.4~3.2mm; main pulse peak current 180~240A, main pulse base current 60~90A, main pulse frequency 50~80Hz; secondary pulse peak current 220~280A, secondary pulse base current 40~60A, secondary pulse frequency 2~5Hz; welding speed 15~25cm / min; shielding gas is a nitrogen-rich mixture of Ar + 3%~8%N2.

[0027] The intermediate filler layer uses a heat input of 1.0~1.3kJ / mm to maintain a stable fine-grained acicular ferrite structure, achieving a smooth transition in mechanical and corrosion properties between the underlayer and the cover layer. The surface cover layer moderately increases the heat input to 1.2~1.5kJ / mm, combined with high and low frequency dual-pulse synergistic control: the high-frequency main pulse controls the droplet transition and penetration depth, while the low-frequency secondary pulse generates a periodic electromagnetic stirring effect in the molten pool, breaking up columnar crystals and promoting the formation of equiaxed crystals, resulting in a uniform and fine equiaxed crystal structure in the cover weld with a grain size of 8~10. The shielding gas contains 3%~8% N2, which reacts with nitrogen at the high welding temperature to generate rare earth nitrides (REN), which work synergistically with rare earth oxysulfides to further refine the grains and improve corrosion resistance. Meanwhile, the solid solution strengthening effect of nitrogen improves the strength of the weld metal. In order to further optimize the weld formation quality and eliminate welding inclusion defects, this process is equipped with AC square wave TIG welding, which utilizes the cathodic cleaning effect of the negative half-cycle on the surface of the molten pool to remove oxide film, reduce inclusions, and improve the surface quality of the weld.

[0028] The entire welding process employs a gradient distribution of "low heat input for root pass → medium heat input for fill pass → medium-high heat input for top pass." By gradually increasing the heat input, the gradient optimization of the microstructure from the root to the surface is achieved: low heat input at the root ensures a fine-grained microstructure, while appropriately increasing the heat input at the surface promotes the full reaction of rare earth elements and the formation of nitrides, while avoiding grain coarsening caused by excessive overall heat input.

[0029] Step S4, Ultrasonic Impact Nanoscale Treatment: After welding, an ultrasonic impact gun is used to impact the weld surface and the heat-affected zone within 15-25 mm on both sides. The impact frequency is 20-28 kHz, the impact amplitude is 30-50 μm, and the impact is repeated 2-4 times at a speed of 150-300 mm / min, so that the surface coverage of the treated area is ≥95%. The ultrasonic impact introduces strong plastic deformation into the weld surface layer, thereby forming a nanocrystalline layer with a grain size of 10-100 nm and a thickness of 50-200 μm on the weld surface layer. The layer has a large number of grain boundaries, which promotes the formation of a dense passivation film and improves corrosion resistance. The ultrasonic impact treatment uses an impact needle with a diameter of φ2 to 4 mm to perform reciprocating impact. The ultrasonic impact treatment introduces a residual compressive stress layer with a depth of 400 to 600 μm on the surface of the weld, with a maximum residual compressive stress of -300 to -500 MPa, which offsets the residual tensile stress of welding and reduces the susceptibility to stress corrosion cracking. The ultrasonic impact treatment reduces the surface roughness Ra of the weld from 12 to 20 μm in the weld state to 2 to 4 μm, reducing the retention of corrosive media on the surface and the formation of local concentration cells.

[0030] Step S5, Electrochemical In-situ Passivation Treatment: Utilizing the high-density grain boundaries in the nanocrystalline layer formed in Step S4 as nucleation sites for the passivation film, constant potential electrochemical passivation treatment is performed on the weld surface. The treatment solution is a mixed solution of 0.5~2.0 mol / L NaNO3 and 0.1~0.5 mol / L Ce(NO3)3, with a solution temperature of 40~60℃, a constant potential of +0.2~+0.6V (vs. SCE), and a treatment time of 10~30 min. A composite passivation film containing CeO2 and Ce2O3 is formed on the weld surface, resulting in a rare earth pipeline steel welded joint. The welded joint is placed in a 3.5wt% NaCl corrosion solution, and the self-corrosion potential difference between the weld area and the base material is ≤30mV.

[0031] In this electrochemical in-situ passivation treatment, Ce in the solution 3+ A stable redox reaction occurs on the weld surface, generating CeO2 and Ce2O3 rare earth oxides in situ, which are uniformly embedded within the iron-based passivation film, forming an Fe-Ce composite oxide passivation layer. The weld surface potential is controlled within the passivation region (+0.2~+0.6V vs. SCE) using a potentiostat, avoiding pitting corrosion due to over-passivation or activation dissolution due to under-passivation, thus achieving precise control over the passivation film thickness and composition. Simultaneously, the high chemical stability and oxygen ion conductivity of rare earth oxides significantly improve the density and self-healing ability of the passivation film.

[0032] Based on the nanocrystalline surface layer formed by ultrasonic impact, the passivation film formed by electrochemical treatment has a stronger bond with the substrate, forming a gradient structure of "nanocrystalline substrate + dense rare earth composite passivation film", which improves corrosion resistance by 3 to 5 times compared with single treatment.

[0033] The ultrasonic shock and electrochemical in-situ passivation in this application are not simply sequential additives, but exhibit a significant synergistic effect: the nanocrystalline layer introduced by ultrasonic shock has high-density grain boundaries and dislocations, providing a large number of active sites for the electrochemical passivation reaction and promoting the uniform and rapid formation of the passivation film; the residual compressive stress introduced by ultrasonic shock inhibits stress cracking during the passivation film growth process, improving film integrity; and the Ce in the electrochemical treatment... 3+ Segregation towards grain boundaries fills nanoscale grain boundary defects, hindering the penetration of corrosive media along the grain boundaries; the composite protective layer formed by the two synergistically has a thickness of 80~150nm, reducing the self-corrosion current density to 10. -7 A / cm 2 The magnitude of the corrosion potential difference between the weld and the base material is stabilized within 30mV, eliminating galvanic corrosion defects in the weld joint, in conjunction with the pretreatment process.

[0034] The constant potential electrochemical passivation treatment adopts a three-electrode system, with the working electrode being the weld itself, the auxiliary electrode being a Pt sheet, and the reference electrode being a saturated calomel electrode.

[0035] The accompanying testing methods in this application are used to verify the joint's resistance to galvanic corrosion, and three types of electrochemical tests can be used to determine whether the process meets the standards: (1) Micro-area electrochemical scanning test: Micro-area current density scanning was performed on each region (WM, FZ, CGHAZ, FGHAZ, BM) of the weld joint using a scanning electrochemical microscope (SECM) or scanning vibrating electrode technique (SVET) to evaluate electrochemical uniformity. Acceptance standard: Current density range between regions ≤ 50 μA / cm². 2 ; (2) Electrochemical Impedance Spectroscopy (EIS) Test: The EIS spectra of each region of the welded joint were tested in a simulated corrosive medium (3.5% NaCl solution or 3% NaCl solution containing saturated CO2). Acceptance Criterion: Passivation film resistance Rp ≥ 10 Ω·cm 4 Ω·cm 2 Charge transfer resistance Rct ≥ 10 3 Ω·cm 2 .

[0036] (3) Galvanic corrosion test: The weld metal is coupled to the base metal at a 1:1 area ratio, and the galvanic current density is tested in a simulated corrosive medium. Acceptance standard: Galvanic current density ≤ 1 μA / cm² 2 There was no accelerated anodic dissolution in the weld metal.

[0037] This application provides the following embodiments to further illustrate the technical solution of this application, but this application is not limited to the following embodiments.

[0038] Example 1 (X65 Rare Earth Pipeline Steel) The base material is 12mm thick X 65 grade rare earth pipeline steel with a V-shaped bevel, a bevel angle of 60°, a blunt edge of 2mm, and a root gap of 2mm. The chemical composition of the base material (mass%) is: C 0.07, Si 0.25, Mn 1.45, P 0.010, S 0.003, Cr 0.35, Ni 0.25, Mo 0.15, Nb 0.040, Ti 0.015, RE 0.012, Cu 0.20, with the balance being Fe.

[0039] Steel ingots for welding wire were prepared by vacuum induction melting. The chemical composition (mass%) of the welding wire was as follows: C 0.05, Si 0.30, Mn 1.30, Cr 0.50, Ni 1.10, Mo 0.35, Nb 0.035, Ti 0.012, RE 0.022 (Ce:La=65:35), Cu 0.25, S 0.003, P 0.008, with the balance being Fe. The wire was forged, hot-rolled, and drawn to φ1.2mm, and then copper-plated on the surface.

[0040] Step S2, Pulsed MIG root pass welding: Pulse frequency 120Hz, peak current 300A, base current 100A, duty cycle 40%, welding speed 30cm / min, heat input 1.0kJ / mm, shielding gas Ar+3%CO2+1%O2, single-sided welding, back side Ar protection, 1 root pass.

[0041] Step S3, Double-pulse TIG filler and capping: main pulse frequency 60Hz, main pulse peak current 200A / base current 70A, secondary pulse frequency 3Hz, secondary pulse peak current 250A / base current 50A, welding speed 20cm / min, heat input 1.2kJ / mm, shielding gas Ar+5%N2, tungsten electrode φ2.4mm, 2 filler layers and 1 capping layer.

[0042] Step S4, Ultrasonic Impact Nanoforming Treatment: A 20kHz ultrasonic impact gun with an amplitude of 40μm, an impact needle of φ3mm, and an impact moving speed of 200mm / min was used to perform three reciprocating impacts, resulting in a surface coverage rate of ≥98%. After treatment, the surface roughness Ra=3.2μm, the surface nanocrystal size is approximately 50nm, and the residual compressive stress is -420MPa.

[0043] Step S5, Electrochemical in-situ passivation treatment: The passivation solution is 1.0 mol / L NaNO3 + 0.3 mol / L Ce(NO3)3, the solution temperature is 50℃, the constant potential is +0.4V (vs. SCE), and the treatment time is 20 min; after treatment, a uniform blue-purple Fe-Ce composite passivation film is formed on the weld surface.

[0044] Electrochemical test results: The self-corrosion potential difference between the weld and the base material in 3.5wt% NaCl solution is 22mV, which meets the performance index of ≤30mV, and the joint has no obvious tendency for galvanic corrosion.

[0045] Example 2 (X70 rare earth pipeline steel) The base material is 16mm thick X70 grade rare earth pipeline steel, with an X-shaped bevel, a bevel angle of 55°, and a blunt edge of 3mm. The chemical composition of the base material (mass%) is: C 0.06, Si 0.28, Mn 1.55, P 0.008, S 0.002, Cr 0.40, Ni 0.30, Mo 0.18, Nb 0.045, Ti 0.018, RE 0.015, Cu 0.22, with the balance being Fe.

[0046] Chemical composition of welding wire (mass%): C 0.04, Si 0.35, Mn 1.40, Cr 0.55, Ni 1.25, Mo 0.40, Nb 0.040, Ti 0.015, RE 0.025 (Ce:La=62:38), Cu 0.30, S 0.002, P 0.006, balance Fe; drawn to φ1.0mm.

[0047] Step S2, Pulsed MIG root pass: Pulse frequency 100Hz, peak current 320A, base current 90A, duty cycle 45%, welding speed 35cm / min, heat input 0.9kJ / mm, shielding gas Ar+2%CO2+0.8%O2.

[0048] Step S3, Double-pulse TIG filler and capping: main pulse frequency 70Hz, main pulse peak current 220A / base current 80A, secondary pulse frequency 4Hz, secondary pulse peak current 260A / base current 55A, welding speed 18cm / min, heat input 1.3kJ / mm, shielding gas Ar+6%N2, tungsten electrode φ3.2mm, 3 filler layers and 1 capping layer.

[0049] Step S4, Ultrasonic Impact Nanoforming Treatment: Impact frequency 22kHz, amplitude 45μm, impact needle φ2.5mm, impact moving speed 250mm / min, reciprocating impact 4 times; after treatment, the surface nanocrystal size is about 30nm, and the residual compressive stress is -480MPa.

[0050] Step S5, Electrochemical in-situ passivation treatment: The passivation solution is 1.5 mol / L NaNO3 + 0.4 mol / L Ce(NO3)3, the solution temperature is 55℃, the constant potential is +0.5V (vs. SCE), and the treatment time is 25 min.

[0051] Electrochemical test results: The self-corrosion potential difference between the weld and the base material in 3.5wt% NaCl solution is 18mV, which meets the performance index of ≤30mV, and the joint has no obvious tendency for galvanic corrosion.

[0052] This application constructs a triple-coupled composite welding system consisting of "electrochemically matched rare-earth welding wire + segmented dynamic pulse welding + ultrasonic impact-electrochemical in-situ passivation," solving the technical problems of uneven potential, susceptibility to galvanic corrosion, and poor weld corrosion resistance in rare-earth pipeline steel welded joints. By precisely controlling the electrochemical performance of the weld using Ce-La mixed rare-earth modified welding wire, the self-corrosion potential difference between the weld and the base material is stably controlled within 30mV, eliminating macroscopic galvanic corrosion. The rare-earth-generated oxysulfides and nitrides refine the weld grains and purify grain boundary defects, reducing microscopic corrosion galvanic cells and achieving uniform electrochemical performance across the entire joint, overcoming the drawback of traditional welding's "weld-priority corrosion." Simultaneously, ultrasonic nano-sizing and rare-earth electrochemical passivation form a significant synergistic effect, constructing a dense, self-healing Fe-Ce composite gradient passivation film on the weld surface, effectively resisting chloride ion erosion, significantly reducing the corrosion rate of the welded joint, and greatly improving the joint's corrosion resistance.

[0053] This application employs a gradient heat input process of "low heat input for the initial layer, medium heat input for the final layer, and medium-high heat input for the final layer," combined with dual-pulse electromagnetic stirring, nitrogen solid solution strengthening, and AC cathodic cleaning technology. This effectively suppresses grain coarsening, eliminates welding inclusions, and yields a uniform and fine gradient grain structure, ensuring the joint possesses excellent strength and toughness. Ultrasonic impact treatment effectively offsets residual tensile stress from welding, optimizes surface roughness, and introduces stable residual compressive stress, significantly reducing the risk of stress corrosion and localized corrosion. The entire process is simple, requiring no post-weld heat treatment or additional protective coatings, and is adaptable to various rare-earth pipeline steels for on-site construction. While ensuring the joint possesses both excellent corrosion resistance and mechanical properties, it also reduces construction costs.

[0054] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of this application.

Claims

1. A composite welding method for rare earth pipeline steel to resist electrochemical corrosion, characterized in that, Using rare earth pipeline steel as the base material, welding is performed using specialized welding wire, and includes the following steps: Step S1, Pre-welding treatment: Grind and clean the steel bevel and both sides of the rare earth pipeline to remove oxide scale, oil and impurities, and expose the metal luster. Step S2, Pulsed MIG root pass welding: Pulsed gas inert metal arc welding is used for root pass welding. The heat input is controlled at 0.8~1.2kJ / mm to obtain a uniform and fine composite structure of acicular ferrite and granular bainite in the root pass weld. Step S3, Double-pulse TIG filler and capping weld: Using AC double-pulse tungsten inert gas (TIG) shielded welding, intermediate filler weld and surface capping weld are sequentially performed on the root weld. The heat input of the intermediate filler weld is controlled at 1.0~1.3 kJ / mm, so that the filler weld forms a microstructure mainly composed of acicular ferrite. The heat input of the surface capping weld is controlled at 1.2~1.5 kJ / mm, so that the capping weld forms a microstructure mainly composed of equiaxed ferrite with dispersed carbonitride precipitates. Step S4, Ultrasonic Impact Nanoscale Treatment: After welding, use an ultrasonic impact gun to impact the weld surface and the heat-affected zone within 15-25mm on both sides. The impact frequency is 20-28kHz, the impact amplitude is 30-50μm, and the impact is repeated 2-4 times at a speed of 150-300mm / min to make the surface coverage of the treated area ≥95%, thereby forming a nanocrystalline layer with a grain size of 10-100nm and a thickness of 50-200μm on the weld surface. Step S5, Electrochemical In-situ Passivation Treatment: Utilizing the high-density grain boundaries in the nanocrystalline layer formed in Step S4 as nucleation sites for the passivation film, constant potential electrochemical passivation treatment is performed on the weld surface. The treatment solution is a mixed solution of 0.5~2.0 mol / L NaNO3 and 0.1~0.5 mol / L Ce(NO3)3, with a solution temperature of 40~60℃, a constant potential of +0.2~+0.6V (vs. SCE), and a treatment time of 10~30 min. A composite passivation film containing CeO2 and Ce2O3 is formed on the weld surface, resulting in a rare earth pipeline steel welded joint.

2. The composite welding method for resisting electrochemical corrosion of rare earth pipeline steel according to claim 1, characterized in that, The welding wire is a Ce-La mixed rare earth modified low alloy high-strength steel welding wire, with the following chemical composition by mass percentage: C 0.03~0.06%, Si 0.20~0.40%, Mn 1.10~1.50%, Cr 0.50~0.55%, Ni 1.10~1.25%, Mo 0.35~0.40%, Cu 0.25~0.30%, Nb 0.035~0.040%, Ti 0.012~0.015%, S≤0.004%, P≤0.010%, with the balance being Fe and unavoidable impurities; Ce and La in the welding wire constitute mixed rare earth RE, with a total mass fraction of Ce and La of 0.015%~0.030%, and a Ce to La mass ratio of (60~70):(30~40).

3. The composite welding method for resisting electrochemical corrosion of rare earth pipeline steel according to claim 1, characterized in that, The chemical composition of the rare earth pipeline steel base material, by mass percentage, is as follows: C 0.04~0.07%, Si 0.20~0.35%, Mn 1.40~1.65%, Cr 0.35~0.40%, Ni 0.25~0.30%, Mo 0.15~0.18%, Cu 0.20~0.22%, Ce and La total rare earth RE mass fraction of 0.010%~0.015%, Nb 0.040~0.045%, Ti 0.015~0.018%, S≤0.005%, P≤0.015%, with the balance being Fe and unavoidable impurities.

4. The composite welding method for resisting electrochemical corrosion of rare earth pipeline steel according to claim 1, characterized in that, In step S2, the process parameters for pulsed MIG root pass welding are as follows: wire diameter φ1.0~1.2mm, peak current 280~350A, base current 80~120A, pulse frequency 80~150Hz, pulse duty cycle 35%~50%, welding speed 25~40cm / min, and shielding gas is a ternary mixture of Ar + 2%~5%CO2 + 0.5%~1.5%O2.

5. The composite welding method for resisting electrochemical corrosion of rare earth pipeline steel according to claim 1, characterized in that, In step S3, the process parameters for dual-pulse TIG filler and capping welding are as follows: tungsten electrode diameter φ2.4~3.2mm; main pulse peak current 180~240A, main pulse base current 60~90A, main pulse frequency 50~80Hz; secondary pulse peak current 220~280A, secondary pulse base current 40~60A, secondary pulse frequency 2~5Hz; welding speed 15~25cm / min; shielding gas is a nitrogen-rich mixture of Ar + 3%~8% N2.

6. The composite welding method for resisting electrochemical corrosion of rare earth pipeline steel according to claim 1, characterized in that, The ultrasonic impact treatment in step S4 introduces a residual compressive stress layer with a depth of 400~600μm on the surface of the weld, with a maximum residual compressive stress of -300~-500MPa.

7. The composite welding method for resisting electrochemical corrosion of rare earth pipeline steel according to claim 1, characterized in that, The ultrasonic impact treatment in step S4 reduces the surface roughness Ra of the weld from 12~20μm in the welded state to 2~4μm.

8. The composite welding method for resisting electrochemical corrosion of rare earth pipeline steel according to claim 1, characterized in that, Step S4, ultrasonic impact treatment, uses an impact needle with a diameter of φ2~4mm to perform reciprocating impact.

9. The composite welding method for resisting electrochemical corrosion of rare earth pipeline steel according to claim 1, characterized in that, In step S5, the constant potential electrochemical passivation treatment adopts a three-electrode system, with the working electrode being the weld itself, the auxiliary electrode being a Pt sheet, and the reference electrode being a saturated calomel electrode.

10. The composite welding method for resisting electrochemical corrosion of rare earth pipeline steel according to claim 1, characterized in that, The welded joint is placed in a 3.5wt% NaCl corrosion solution, and the self-corrosion potential difference between the weld area and the base material is ≤30mV.